Analysis of visual search features. (1st January 2012) - Saha, Pradipta Kumar; Samanta, Debasis; Sarcar, Sayan; Sharma, Manoj Kumar
While user accesses a user interface, visually searching for a particular object is inevitably accomplished. Visually searching for information, one of the fastest and most useful way of finding information over a variety of user interfaces is driven by different features associated with it. Further, the level of significances of a feature may vary from one interface to another. This paper proposes an exhaustive way to identify visual features associated with virtual keyboard interfaces. First, we list all visual features which user interface designers usually refer. Next, a user-based evolution has been carried out to find out the applicability of different visual features in the context of virtual keyboard interfaces. Finally, we identify visual features having considerable impact on visual search task, related to virtual keyboards. Outcome of this research would be useful to develop a computational model to predict visual search time, which then can be applied to evaluate virtual keyboard designs.